Matched Pairs Comparison of an Enhanced Recovery Pathway Versus Conventional Management on Opioid Exposure and Pain Control in Patients Undergoing Lung Surgery. Issue 6 (December 2021) - Rice, David; Rodriguez-Restrepo, Andrea; Mena, Gabriel; Cata, Juan; Thall, Peter; Milton, Denai; Correa, Arlene; Woodard, TaCharra; Antonoff, Mara; Hofstetter, Wayne; Roth, Jack; Sepesi, Boris; et al.
Abstract : Objective: The aim of this study was to assess the effect of an enhanced recovery after surgery (ERAS) pathway on pain and opioid use following lung resection. Summary Background Data: A major component ERAS pathways is opioid-sparing analgesia; however, the effect on postoperative pain and opioid use in patients undergoing lung resection is unknown. Methods: Following implementation of an ERAS pathway for lung resection, 123 consecutive patients were identified. Patients were propensity-matched 1:1 with a group of consecutive patients (n = 907) undergoing lung resection before ERAS. Differences regarding in-hospital opioid consumption, discharge prescribing of opioids, and postoperative pain scores were examined. Morphine milligram equivalents were separately calculated including and excluding tramadol as an opioid medication. Results: There were no significant differences between matched patients regarding age, sex, performance status, receipt of preoperative treatment, extent of lung resection, or operative approach. Epidural analgesia was used in 66% of controls and in none of the ERAS group ( P < 0.001). The number of adjunct analgesics used postoperatively was greater in the ERAS group (median 3 vs 2, P < 0.001). There was a major reduction in morphine milligram equivalents in the ERAS group whether tramadol was included (median 14.2 vs 57.8, P < 0.001) or excluded (median 2.7 vs 57.8, P < 0.001) and regardless of surgical approach. Average daily pain scores were lower in the ERAS group (median 1.3 vs 1.8, P = 0.004); however, this difference was present only among patients undergoing thoracotomy. The proportion of patients who were prescribed discharge opioids varied whether tramadol was included (96% each group, P = 1.00) or excluded (39% vs 80%, P < 0.001) in the analysis. Conclusions: Implementation of an ERAS pathway was associated with effective post-operative analgesia, major reductions in in-hospital consumption of opioids, and reduced pain, compared to conventional management. Abstract : Supplemental Digital Content is available in the text